Selected papers from CONSAL XII in Brunei - Paul, Johnson; Tedd, Lucy A. (Program: electronic library and information systems., 2004)
This editorial provides brief background information on the Congress of Southeast Asian Librarians and its twelfth conference which was held in Brunei Darussalam in October 2003. In April 2004 Rasu Ramachandran, who had been Secretary General of CONSAL and the Director of the National Library of Singapore at the time of CONSAL XII, became Secretary General of the International Federation of Library Associations and Institutions (IFLA), and a report of an interview conducted with him prior to taking up his new post is included.